Socioeconomic and environmental impact of glyphosate spraying for coca crop eradication (Revista "Boletín el Conuco", 2024)
Drug trafficking in Colombia has been present for more than fifty years, when the marijuana boom was unleashed and has intensified with the con- tinued global demand for cocaine, which gener- ated concern for governments. For this reason, since the 1980s, governments have declared war on it through the implementation of anti-drug policy strategies. For years, the fight against drugs focused primarily on eliminating illicit crops through aerial spraying of glyphosate, a herbicide whose use has been controversial and has sparked a national debate questioning its effectiveness in reducing the areas planted with coca. In this context, the objective was to analyze the environmental and socioeconomic impact of aeri- al spraying with glyphosate. Therefore, the meth- odology was carried out through a documentary review with the collection, analysis and interpre- tation of the information obtained. The results showed that glyphosate represents a threat to the health of the population, the environment and the subsistence economy of the peasant families, who have had or have coca crops. For this reason, the implementation of this strategy, besides being too costly, has been counterproductive.
Keywords: Drug trafficking; debate; glyphosate; impact; illicit crops; anti-drug policy